Engenia Applied Preemergence & Postemergence for Weed Control in Soybean. - Damian Franzenburg; Iththiphonh Macvilay (Hello World!, 2024)
The purpose of this study was to compare weed control of Engenia herbicide used at different application timings within various two-pass application programs; Engenia was applied Preemergence (PRE), early postemergence (EPOST) and postemergence (POST) for weed control in corn.